Magma mobilization by downward-propagating decompression of the Eyjafjallajökull volcanic plumbing system - Tarasewicz, J. P. T.; White, R. S.; Woods, A. W.; Brandsdóttir, B.; Gudmundsson, M. T. (Geophysical Research Letters, 2012)
Detailed observations of the 2010 Eyjafjallajökull eruptions in Iceland show seismic activity propagating vertically through the entire crust during a ten-week period of volcanic unrest comprising multiple eruption episodes. Systematic changes in magma chemistry suggest a complex magmatic plumbing system, tapping several accumulation zones at different depths containing magma of differing ages and compositions. During the eruption, a systematic downward propagation of seismicity through the crust and into the upper mantle to ~30 km depth occurred in a series of steps, each of which preceded an explosive surge in eruption rate. Here we show that the sequence of seismicity and eruptive activity may be explained by the downward propagation of a decompression wave that triggers magma release from progressively deeper sills in the crust. Comparing observations of the downward-propagating seismicity with the decompression of a series of model elastic sills suggests that each sill was 1-10 km3 in size.